(untitled) (Research, Society and Development, 2021)
The objective of this study was to verify the influence of digital videos, using the Edpuzzle tool, on the performance of accounting students. This technological resource was used in four subjects of the Accounting Science Course through the students cell phones. The research used a quantitative approach, with the participation of 164 students. The study consisted of a quasi-experiment, with two tests being applied, called pre-test and post-test, in order to compare the performance between the control and experimental groups. The statistical results indicated that there were no significant differences between the groups, similar information was obtained when crossing between the pre-test and post-test scores. The findings, despite not confirming the hypothesis of improvement in academic performance with the use of technology and, especially the videos conducted in Edpuzzle, suggest that there was significant motivation and satisfaction on the part of students in carrying out the requested tasks. Considering the limitations of the research, specifically in relation to the context and the period of application, it can be said that its main contribution was the perception that the use of a certain technology in the classroom, by itself, does not improve performance and that more studies are needed with different methodological approaches and in extended periods and samples.